PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA PADA PELAJARAN IPA KELAS IV SD NEGERI INPRES 6.88 PERUMNAS II YABANSAI - Gaol, Diana Lumban (Magister Pendidikan IPA, UNCEN, 2015)
Abstract. Purpose of this study was to determine: (1) Differences in student motivation instruction IV SDN Inpres 6.88 Perumnas II grade applied jigsaw cooperative learning model with conventional method (2) Differences in student learning outcomes instruction IV SDN Inpres 6.88 Perumnas II grade applied jigsaw cooperative learning model with conventional method (3) Improving student learning outcomes after the IV grade SDN Inpres 6.88 Perumnas II applied jigsaw cooperative learning with the conventional method.This research uses quasi expermental design analysis method, with this type of design non equivalent pre test-post test The results showed that: (1) There are differences in student motivation class IV SDN Inpres 6.88 Perumnas II applied jigsaw cooperative learning model and compared with conventional models. In the data processing included in both categories. The results of the statistical calculation shows that the count sig 0.000